2022
DOI: 10.1108/jefas-04-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the world stock indices' co-movements by association rule mining

Abstract: PurposeThis study aims to provide preliminary information to the investor by determining which indices co-movement, with the data mining method.Design/methodology/approachIn this context, data sets containing daily opening and closing prices between 2001 and 2019 have been created for 11 stock market indexes in the world. The association rule algorithm, one of the data mining techniques, is used in the analysis of the data.FindingsIt is observed that the US stock market indices take part in the highest confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Karaatlı et al (2021) stated that in order to create a portfolio, shares in the BIST 30 index are included in macroeconomic variables (M1 money supply, gold ounce price, export-import coverage ratio, industrial production index, foreign exchange basket, manufacturing industry capacity utilization rate, interest, producer price index, financial FP-Growth algorithm was used to analyze its movement with services confidence index, international direct investments, crude oil, S&P 500 index). In their study, Kartal et. al.…”
Section: An Investigation Of Co-movements Of Commodity Markets By Dat...mentioning
confidence: 93%
“…Karaatlı et al (2021) stated that in order to create a portfolio, shares in the BIST 30 index are included in macroeconomic variables (M1 money supply, gold ounce price, export-import coverage ratio, industrial production index, foreign exchange basket, manufacturing industry capacity utilization rate, interest, producer price index, financial FP-Growth algorithm was used to analyze its movement with services confidence index, international direct investments, crude oil, S&P 500 index). In their study, Kartal et. al.…”
Section: An Investigation Of Co-movements Of Commodity Markets By Dat...mentioning
confidence: 93%
“…As another promising data science technique, association rule mining can also be used for making decisions in financial institutions (Pawar et al, 2019;Chen et al, 2022;Kartal et al, 2022). The association rule mining aims to discover a pattern of frequently used items appearing together in data sets.…”
Section: Introductionmentioning
confidence: 99%
“…For their part, Kartal et al (2022) demonstrated that the world stock indices have co-movement, and this continues as a cycle. Likewise, to make the right investment decision, investors must consider market mobility to form financial markets resistant to economic shocks.…”
mentioning
confidence: 99%